Risk Factors and Postoperative Complications of Lobectomy for Non-Small Cell Lung Cancer: An Exploratory Analysis of Premedication and Clinical Variables - Kepičová, Markéta; Tulinský, Lubomír; Kondé, Adéla; Dzurňáková, Paula; Ihnát, Peter; Adamica, Dávid; Neoral, Čestmír; Martínek, Lubomír (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Postoperative pneumonia and complications significantly impact outcomes in thoracic surgery, particularly for patients undergoing lobectomy for non-small cell lung cancer (NSCLC). This study evaluates whether preoperative premedication influences the risk of postoperative pneumonia and overall complications. Materials and Methods: This retrospective study included 346 patients who underwent lobectomy for NSCLC at the University Hospital Ostrava between 2015 and 2021. Data on demographic variables, tumour staging, surgical approach, and premedication (anticholinergics, benzodiazepines, antihistamines, and analgesics) were analysed. Postoperative outcomes included pneumonia and complications classified by the modified Clavien-Dindo system. Results: Premedication was not significantly associated with postoperative pneumonia (10.7%) or overall complications (26.0%). Tumour size was the only factor significantly associated with complications, with larger tumours increasing the odds (OR: 1.16, p = 0.032). Other factors, including age, ASA classification, BMI, and surgical approach, did not demonstrate significant associations with postoperative outcomes. Conclusions: Premedication does not appear to significantly influence the risk of postoperative pneumonia or overall complications in patients undergoing lobectomy for NSCLC. Similarly, other clinical variables, such as age, ASA classification, BMI, and surgical approach, also did not show significant associations with these outcomes. These findings suggest that premedication can be individualised without increasing postoperative risks. However, tumour size emerged as a significant factor associated with complications, highlighting the need for careful preoperative assessment and planning, particularly in patients with larger tumours.
Keywords: risk factors; postoperative complication; nádory plic; nemalobuněčný karcinom plic; Pneumonectomy; lung cancer; Lung Neoplasms; Humans; thoracic surgery; lidé středního věku; Carcinoma, Non-Small-Cell Lung; premedikace; pneumonie; rizikové faktory; Female; dospělí; Aged; lobectomy; senioři; lidé; premedication; pneumektomie; Postoperative Complications; Adult; pooperační komplikace; postoperative pneumonia; ženské pohlaví; Pneumonia; Male; Middle Aged; Retrospective Studies; Premedication; Aged, 80 and over; senioři nad 80 let; retrospektivní studie; mužské pohlaví; Risk Factors